Material Culture of the Jesuits in Vilnius: Between the Religious Ideal and Social Reality - Mariani, Andrea (Senoji Lietuvos literatūra, 2020)
This article analyzes the material culture of the Jesuits in Vilnius during the second half of the eighteenth century. Based on the manuscript inventories of Jesuit houses issued after the suppression of the Society of Jesus in 1773, the author examines the furniture and internal decoration of the Academic college next to St John’s Church, the professed house near St Casimir’s Church, the novitiate house next to St Ignatius’ Church, and the tertianship house nearby St Raphael’s Church. Attention is focused on paintings, heating systems, furniture, and tableware. The author attempts to assess the extent to which the Jesuit material culture was an expression of religious ideals. Moreover, since an increasing number of Jesuits came from noble families, the author considers whether the habits acquired at home before entering the Jesuit Order influenced the material culture of the Jesuit houses. Finally, the author seeks to verify whether the equipment of the Jesuit houses in Vilnius was richer or more modern than their equivalents in the province. Paintings enhanced religious piety, created a sense of unity among the religious community, and preserved the memory of its benefactors. Heating systems were based on a combination of fireplaces and tiled stoves, particularly suitable to the cold climate of the region. Fashionable tiled stoves defined as Saxon stoves (piece saskie) were located in the more richly decorated rooms, where guests were received. In the eighteenth century, new and more specialized pieces of furniture appeared, such as sofas, clocks, and folding tables. Unlike in the houses of the nobles, where broken clocks were sometimes displayed as status symbols, in the Jesuit houses these items had to be functional, since they regulated activities of the whole community. Tableware reflected the changes occurring in eighteenth-century eating culture when such new products as coffee, tea, and chocolate became more popular throughout the Polish-Lithuanian Commonwealth. This prompted the appearance of new items, such as teacups and teapots. Food became less spiced and could be seasoned at the table, thus creating the need for new vessels like sugar-bowls and sauceboats. All these new items were available in Jesuit houses, albeit new drinks were treated more as medicines rather than ordinary items of consumption. New materials (glass and porcelain) also became more available, gradually superseding silver and tin. In this field, Jesuits continued to prefer tin and to some extent glass; porcelain was not used, while silver was associated to the religious sphere. On the basis of these considerations, the author concludes that Jesuit material culture was largely autonomous from that of the nobility. Due to the poverty vow, items had to be durable, but not ostentatious. Even when Jesuits possessed items that were popular among upper social layers, they lent these items a different meaning, which was more suitable to the needs and ideals of a religious order. Finally, the level of material culture was diverse among the houses of Vilnius Jesuits. Due to their public role, the Academy and the professed house were more richly equipped than the novitiate and the tertianship houses. The author observes that the Academy and the professed house did not differ from other major colleges in the Lithuanian Province.